Editorial - Pacheco-Romero, José (2017)
This Editorial has been updated due to the severe consequences of the ‘El Niño costero’ (Coastal El Niño Phenomenon) that is devastating Peruvian and Ecuadorian coasts due to the increase in the temperature of the Pacific Ocean and the intense rain that it causes in the highlands. Rain results in flooded streets, cities and farmlands, and “huaycos”, large masses of mud and rocks detached from the Andes. These descend from the highlands at great speed, mainly due to gorges formed over the centuries, dragging everything in their path. According to the National Emergency Operation Center (Centro de Operaciones de Emergencia Nacional – COEN), up to March 20, the phenomenon has caused 75 deaths, 100 000 victims, and 134 125 damaged homes, mainly in the coast of Peru. Drinking water and electricity are limited or absent, but national and international solidarity is present.